An Andean-type retro-arc foreland system beneath northwest South China revealed by SINOPROBE profiling - Li, Jianhua; Dong, Shuwen; Cawood, Peter A.; Zhao, Guochun; Johnston, Stephen T.; Zhang, Yueqiao; Xin, Yujia (Earth and planetary science letters, 2018)
In the Mesozoic, South China was situated along the convergent margin between the Asian and Pacific plates, providing an excellent laboratory to understand the interactions between deformation, sedimentation and magmatism in a retroarc environment. The crustal architecture of northwest South China is displayed along the ∼600-km-long SINOPROBE deep seismic reflection profiles and reveals from east to west: (1) highly folded and truncated reflectors in the upper crust of the Yangtze Fold Zone, which correspond to thin- and thick-skinned thrust systems, and document large-scale intraplate structural imbrication and shortening; (2) a crustal-scale flat-ramp-flat structure, termed the Main Yangtze decollement, which forms a weak, viscous layer to accommodate strain decoupling and material transport in the thin- and thick-skinned systems; and (3) nearly flat-lying reflectors in the Sichuan Basin, which support interpretation of the basin as a weakly deformed depocentre. The Yangtze Fold Zone and the Sichuan Basin represent a retro-arc foreland basin system that is >800 km away from the continental-margin magmatic arc. We suggest that tectonic processes across the arc and retro-arc systems, including arc magma flare-up, basin sedimentation, retroarc thrust propagation, lithosphere underthrusting, root foundering, and extension-related magmatism were interrelated and governed mass transfer. Age data and geological relations link the tectonic processes to evolving geodynamics of the subducting Paleo-Pacific plate. •Deep seismic profiles reveal the crustal architecture of northwest South China.•A northwest-tapering retro-arc foreland system is traced in northwest South China.•Tectonic processes in the arc-retroarc system were linked and governed mass transfer.•Intraplate processes were related to subducting geodynamics of the Paleo-Pacific plate.